Enhancing nurses’ communication about psychosocial needs and changes in intimacy and sexuality in patients with advanced cancer: a mixed-method study - Susanne A.M. Arends; Corien M. Eeltink; Floortje K. Ploos van Amstel; Astrid W. Oosten; Donna C. Ruijter; Nelleke van der Loo; Barbara Harterink-Poker; Anneke L. Francke; Irene P. Jongerden (International Journal of Nursing Studies Advances)
Introduction: Patients with advanced cancer often experience psychosocial needs due to the diagnosis or treatment. Despite the importance of these needs, nurses often feel reluctant to address them, especially with regard to changes in intimacy and sexuality. Aim: To evaluate whether hospital nurses’ competences and practices regarding communication about psychosocial needs, including changes in intimacy and sexuality, with patients with advanced cancer, improved after training. Methods: Between 2022 and 2023, we conducted a mixed methods study in six hospitals in The Netherlands. Data were collected three months before and three months after the training course. Perceived competences and documentation regarding communication about psychosocial needs were determined using a survey questionnaire, patient record screening, and semi-structured interviews with nurses. Results: In total 53 hospital nurses participated in the training. Of these participants, 50 nurses completed the survey before the training and 33 after the training. More nurses reported feeling competent in addressing psychosocial needs three months after the training as compared to before (78.8 % and 46.0 %, respectively; p < 0.01), as well as in addressing intimacy (90.9 % and 64.0 %, respectively, p < 0.02) and sexuality (84.8 % and 50.0 %, respectively, p < 0.01). In addition, 83 electronic patient records were screened before the training and 102 after the training. This revealed that only limited notes were made regarding psychosocial needs, and especially regarding changes in intimacy or sexuality. In interviews, nurses mentioned that they felt reluctant to make notes about sensitive topics. Furthermore, they added that they still perceived a lack of time to discuss psychosocial needs, and felt discomfort in addressing intimacy and sexuality. Conclusion: After the programme, more nurses felt competent in discussing psychosocial needs in patients with advanced cancer, especially with regard to changes in intimacy and sexual functioning. The training had little effect on nurses’ notes about psychosocial needs in patient records; the focus remained on physical aspects. Even when they discussed changes in intimacy or sexuality, nurses felt reluctant to document discussions about such sensitive topics.